Industry Based Adaptive Educational Programs - M. G. Ganchenkova; O. V. Boyko (Высшее образование в России)
The aim of this work is to summarize the experience in the development and implementation of industry-oriented educational programs in the field of digital engineering in the educational process.The article presents an example of the interaction of the Higher Engineering School of NRNU MEPhI and the Engineering Division of ROSATOM State Corporation in terms of training for industrial-oriented master programs. The authors present the data on the needs of ROSATOM State Corporation for young personnel in the field of digital engineering, discuss the advantages of the introduction of industrial-oriented master programs in the educational process and the main problems encountered in their development. The article makes the case for collaboration between representatives of the university and the enterprise on the creation and filling of training modules with theoretical and practical material, and gives the main recommendations for solving the emerging difficulties.